FORTIFICATION OF TILAPIA (Oreocrhomis niloticus) FISH MEAL ON CHARACTERISTICS CRACKERS - Ayuningtias widia putri; Sumarto Sumarto; Suparmi Suparmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstrakThis study aims to determine the effect of fortification of tilapia (Oreochromis niloticus) meal on the characteristics of crackers. The method used was an experimental method with a non-factorial completely randomized design study consisting of 4 levels, namely without the addition of fish meal (T0), fortification of 5% tilapia fish meal (T1), 10% fish meal (T2), and fortification of fish meal 15% (T3).The results showed the effect of fortification of tilapia fish meal on the organoleptic characteristics of crackers. Fortification of 15% (57 grams) of tilapia fish meal is the best treatment which results in the characteristics of tilapia crackers having a bright, golden yellow and attractive appearance, delicious and savory taste, crunchy texture, and distinctive aroma of fish crackers. Crackers have a moisture content of 4.43%, 2.32% ash, 28.74% fat, 16.41% protein, and 48.09% carbohydrates.Keyword: crackers, fish meal, Oreocrhomis niloticus